Comparison of cost-effectiveness and postoperative outcomes following integration of a stiff shaft glidewire into percutaneous nephrolithotripsy. (August 2021) - Valadon, Crystal; Abedali, Zain A.; Nottingham, Charles U.; Large, Tim; Krambeck, Amy E.
Aims: To analyze the cost effectiveness of integrating a stiff shaft glidewire (SSGW) in percutaneous nephrolithotripsy (PCNL) relative to standard technique (ST). This is prudent because healthcare providers are experiencing increased pressure to improve procedure-related cost containment. Methods: ST for PCNL at our institution involves a hydrophilic glidewire during initial percutaneous access and then two new stiff shaft wires. The SSGW is a hydrophilic wire used for initial access and the remainder of the procedure. We collected operating room (OR) costs for all primary, unilateral PCNL cases over a 5-month period during which ST for PCNL was used at a single institution with a single surgeon and compared with a 6-month period during which a SSGW was used. Mean costs for each period were then compared along with stone-free rates and complications. Results: We included 17 total cases in the ST group and 22 in the SSGW group. The average operating room supply cost for the ST group was $1937.32 and $1559.39 in the SSGW group. The net difference of $377.93 represents a nearly 20% decrease in cost. This difference was statistically significant ( p  = 0.031). There was no difference in postoperative stone-free rates (82.4% versus 86.4%, p  = 1.0, respectively) or complications (23.5% versus 13.6%, p  = 0.677, respectively) between ST and SSGW groups. Conclusion: Transitioning to a SSGW has reduced OR supply cost by reducing the number of supplies required. The change in wire did not affect stone-free rates or complications.